Evaluate the factors that impact Vietnamese customer’s buying decision for non-life insurance product. - Phan, Minh Hải (2020)
In this research, the author aims examine the factors that affect the customers’ inclination and purchase decision on non-life insurance products and measure the different impacts weights of these factors, based on the results to propose some recommendation for insurers to improve service quality in the future. To archive the reliable answer to the research’s question, this study adopts qualitative research method, online survey via social media platform and face-to-face interview was applied to collect the data from 319 respondents. The results suggest that there are two factors indirectly impact on consumer’s purchase decision through consumer’s inclination, which are personal income and risk recognition, and four factors directly impact on the consumer’s final decision, including consumer’s inclination, sale promotion, insurer’s reputation and insurer’ online communication quality. The author suggests some recommendations for insurance companies to enhance business activities, including diversifying products, building a professional consultant teams, and improve companies imagine.